Tafsir Ayat Al-Qur’an Tentang Hijrah - Muhammad Ghufron; Cyndy Aprillindra; Silva Vadila Putri; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explains the interpretation of the Qur'anic verses about the hijrah, by explaining the hijrah, the various types of hijrah, verses that discuss the hijrah, and the interpretation of the Qur'anic verses about the hijrah. Hijrah is an important theme in the Qur'an which is related to physical, spiritual and social movement from one situation to a better one in order to get closer to Allah. In the context of Islamic history, hijrah refers to the movement of the Prophet Muhammad SAW and his companions from Mecca to Medina to escape persecution and achieve religious freedom. Interpretation of hijrah verses, as in QS. Al-Baqarah: 218, QS. An-Nisa: 100, and QS. At-Taubah: 20, emphasizes the importance of steadfast faith, sacrifice and struggle in achieving Allah's approval. Hijrah is seen as a form of obedience that is highly valued by Allah, with a guarantee of great rewards for those who do it with sincere intentions. The interpretation of these verses also contains a spiritual dimension, where hijrah is defined as moving from a state of sin to the path of obedience. Thus, hijrah is not only limited to the physical aspect, but also includes changes in mental and moral attitudes to improve the quality of faith and piety.This abstract explains the concept of hijrah in the Al-Qur'an and its interpretation, covering historical, spiritual and social aspects in the life of a Muslim.